2011
DOI: 10.1021/la204124p
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Analysis of H2O Adsorption on the (110) Surfaces of SnO2, TiO2 and Their Solid Solutions

Abstract: Both associative and dissociative H2O adsorption on SnO2(110), TiO2(110), and Ti-enriched Sn1-xTixO2(110) surfaces have been investigated at low (1/12 monolayer (ML)) and high coverage (1 ML) by density functional theory calculations using the Gaussian and plane waves formalism. The use of a large supercell allowed the simulation at low symmetry levels. On SnO2(110), dissociative adsorption was favored at all coverages and was accompanied by stable associative H2O configurations. Increasing the coverage from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 72 publications
(222 reference statements)
7
51
0
Order By: Relevance
“…The present results on heat of adsorption for pure tin dioxide are very consistent with data reported in the literature. 28 36 no apparent systematic trend was observed as a function of Mn concentration. That is, the adsorption curves show crossovers along the studied coverage range, such that the integral values become quite similar.…”
Section: Resultsmentioning
confidence: 89%
“…The present results on heat of adsorption for pure tin dioxide are very consistent with data reported in the literature. 28 36 no apparent systematic trend was observed as a function of Mn concentration. That is, the adsorption curves show crossovers along the studied coverage range, such that the integral values become quite similar.…”
Section: Resultsmentioning
confidence: 89%
“…Using GGA + U, molecular water adsorption is preferred on Cr 2 O 3 (0 0 0 1) at the lowest coverage, and isoenergetic molecular and dissociative adsorption is found at high coverage, and the rather low dissociation barrier (0.12 eV) allows proton exchanges between the OH groups from ab initio MD simulation [51]. Dissociative H 2 O adsorption is found on SnO 2 (1 1 0) from the lowest to monolayer coverage [52].…”
Section: Water Adsorption On Other Metal Oxide Surfacesmentioning
confidence: 99%
“…Most computational efforts have been focused on the atomistic level, where the "activity" or "inactivity" with respect to the OER has been quantified using density functional theory (DFT). [18][19][20][21][22] To this concern, theoretical studies of inactive (BDD, SnO 2 -Sb and PbO 2 ) and active (IrO 2 and RuO 2 ) anodes revealed that this reactive trend is a tradeoff between the adsorption energies for H 2 …”
mentioning
confidence: 99%